ChemInform Abstract: Sm3S3BO3: The First Sulfide Borate Without S—O and B—S Bonds. Issue 6 (21st January 2016) - Guo, Sheng‐Ping; Chi, Yang; Xue, Huai‐Guo
Abstract: Sm3 S3 BO3 is obtained via solid‐state reaction of a 3:1:3 molar mixture of Sm2 O3, B, and S (evacuated quartz tubes, staged heating at 300—950 °C, 5 h/stage, 10 d; cooling to 300 °C within 5 d).